Application of jawi's script in graphic design platform / Safwan Sufi Shamsul - Shamsul, Safwan Sufi (Faculty of Art and Design, 2020)
Jawi's script has become the identity of the Malays since almost 1000 years ago. Unfortunately. Many Malaysians themselves are confused by the Jawi's script and the Arabic language by assuming the same thing (Osman Affandi,2019). Historically. the arrival of the Arabians and the process of Islamization of Malay Archipelago long time ago have led to the appearances of the Jawi's script. This thing is undeniable as the main source of Islam is the Koran that is present in Arabic (Osman Affandi,2019). Jawi's script has also been studied by many figures in the writing system and one of the figures who are proficient in writing Jawi Is Professor Dr. Kang Kyoung Seok from South Korea. However, the Jawi's script is no longer practiced in the present era full of advanced technology and also many platforms can be used as advertising or promotion by a company. In this case, the Jawi's script is the identity of the Malays and it is also a writing system that has evolved from the first writing system. Therefore, the Jawi script should always be applied in graphic design platform as one of the signs or the identity of the Malays themselves. In graphic design, it has many platforms for us to use Jawi's script itself as branding on products made in Malaysia. signage on street names and every store are available in Malaysia, the publication of a book in every school and more.